Chassis Dynamometer Testing: Addressing the Challenges of New Global Legislation - Galindo, Eduardo (SAE International, 2017)
The book focuses on chassis test bench methods in the context of stringent global regulations such as WLTP and RDE. It provides an in-depth look at test equipment, emissions assessment procedures and the application of technology by the automobile industry to the new requirements.